A Review on Recent Developments on Detection of Fall - Priyanka, K. Paul Mathi; Kumar, K. (Journal of Trends in Computer Science and Smart Technology, 2023)
Remote patient monitoring has always been a difficult problem in the medical field. Fall detection during monitoring is essential because falls are unexpected behaviors that can seriously affect a person's health, particularly those who are older. Accidental falls have moved to the top of the lists of general health issues in the past few decades. A fall detection system, with the emerging development of the technology, aims to decrease the number of deaths, injuries and the economic burden on the healthcare system. This study presents an in-depth analysis of the latest published research on vision-based detection of falls. It also covers the merits, demerits, and challenges of the previous works of vision-based fall detection, and the future scope of the research is also summarized.
Keywords: Fall detection system; Vision-based; Machine learning; Threshold-based; Pose estimation